PENGAMATAN VEKTOR AEDES AEGYPTI INFEKTIF VIRUS DENGUE DI JAKARTA UTARA TAHUN 2022 - Syakhroni Syakhroni; Dwi Sutuningsih; Nurjazuli (Poltekkes Kemenkes Surabaya, 2023)
Dengue Hemorrhagic Fever (DHF) is a public health problem that needs seriousattention, because this disease has high morbidity and mortality rates and has the potential to cause extraordinary events (KLB). Dengue Hemorrhagic Fever cases tend to increase from year to year and have the potential to cause Extraordinary Events, so that the Special Capital Region of Jakarta Province is an endemic area for Dengue Hemorrhagic Fever. Thepurpose of this literature review is to analyze the density of Aedes aegypti mosquitoes, to analyze infective Aedes aegypti mosquitoes, to increase efforts to control DHF vectors and to be aware of an increase in DHF cases.This study uses an observational method. The data source used comes from primarydata taken directly in residential areas, the selected location is the village with the highest IR number and the test sample is examined in the laboratory.Data owned by the DKI Jakarta Health Service, until the end of January 2021, thenumber of Dengue Fever sufferers reached 3,091 people. Meanwhile, in the same period last year, the number of dengue fever sufferers increased by 35%. The mosquito surveywas conducted in areas that have high cases of dengue fever in North Jakarta, namely Warakas Village, Tanjung Priok District. Of the 100 houses that had been visited and a search for adult mosquitoes was carried out, 69 houses were found. The number of Aedes aegypti mosquitoes caught was 17, consisting of 15 females and 2 males. Then a separate extraction process was carried out between female mosquitoes and male mosquitoes to determine whether or not the dengue virus was present. After obtaining the extraction, the samples were then subjected to PCR testing.The results of testing samples of male and female mosquitoes using the PCR methodin the Warakas Village, Tanjung Priok District, obtained negative results (-) for dengue virus. Vector surveys carried out for disease control program implementers need to expand the sampling locations so that they can represent the population in an area